2021
DOI: 10.1093/heapol/czab099
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of geographical access and factors influencing travel time to emergency obstetric care in the urban state of Lagos, Nigeria

Abstract: Previous efforts to estimate the travel time to comprehensive emergency obstetric care (CEmOC) in low- and middle-income countries (LMICs) have either been based on spatial models or self-reported travel time, both with known inaccuracies. The study objectives were to estimate more realistic travel times for pregnant women in emergency situations using Google Maps, determine system-level factors that influence travel time and use these estimates to assess CEmOC geographical accessibility and coverage in Lagos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 55 publications
1
41
0
Order By: Relevance
“…In Lagos, most pregnant women with obstetrical emergencies living in the peripheral rural areas usually travelled to public hospitals around them. 28 In a separate study, we found that travel to care in this settlement type is typically prolonged in the suburbs. 28 This blurring of the so-called ‘urban advantage’, or at least the ‘suburb advantage’, may explain the higher odds of maternal death in hospitals situated in the suburbs.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In Lagos, most pregnant women with obstetrical emergencies living in the peripheral rural areas usually travelled to public hospitals around them. 28 In a separate study, we found that travel to care in this settlement type is typically prolonged in the suburbs. 28 This blurring of the so-called ‘urban advantage’, or at least the ‘suburb advantage’, may explain the higher odds of maternal death in hospitals situated in the suburbs.…”
Section: Discussionmentioning
confidence: 84%
“… 28 In a separate study, we found that travel to care in this settlement type is typically prolonged in the suburbs. 28 This blurring of the so-called ‘urban advantage’, or at least the ‘suburb advantage’, may explain the higher odds of maternal death in hospitals situated in the suburbs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Traffic and poor road conditions, complexities of urban governance for health and living environments of slums and informal settlements further challenge access to critical maternal and newborn health services, especially for the urban poor. 17 21 22 …”
Section: Introductionmentioning
confidence: 99%
“… 23 The result is a ‘know-do’ gap in maternal and perinatal care, 24 with the phenomena of ‘too little too late’ and ‘too much too soon’ occurring in parallel. 25 26 Although large cities also tend to have tertiary care such as teaching hospitals, 17 urban populations differ hugely in terms of their ability to pay for healthcare and other essential services, which in part has contributed to the growth of a diversity of private providers—for-profit and not-for-profit, formal and informal—targeting various population groups in cities. The presence of different categories of providers, while alleviating some pressure on public services, 16 creates challenges for regulating care quality standards across the variety of providers and ensuring affordable, high-quality care within the umbrella of universal health coverage.…”
Section: Introductionmentioning
confidence: 99%